Per Capita GDP, Health Expenditures, and the Income Elasticity of Demand for Health Care in Developing Nations - Benavides, Adolfo (Journal of Applied Business and Economics, 2018)
Using Word Bank’s World Development Indicators data for 130 developing countries and linear and logarithm regression models, this study tests the functional relationship between Per Capita GDP and Per Capita Health Expenditures. Results suggest that health care is neither a luxury nor a necessity for this entire set of countries. However, for nations with an annual per capita GDP less than 2,500 PPP constant 2000 US, and for countries with GDP per capita over 7,000 PPP constant 2000 US, medical care is a necessity. Health care is a luxury in developing nations with annual GDP per capita between 2,501 and 7,000 PPP constant 2000 US.